Struktúra és egyenlőtlenségek a régi államszocializmusban és az újkapitalizmusban - Ferge, Zsuzsa (Szociológiai Szemle, 2024)
The structure of state socialism was stifled by totalitarian power yet inequalities persisted. The stratification by the 'character of the work done', a combination of power/authority, knowledge, working conditions etc. was veiled by the official ideology about the near-equality of two 'classes' and about the abolition of poverty. Social inequalities were studied in the 1960s and 1980s in these terms, showing a structure that was shifting upwards in two decades, where social distances decreased in some respects, but where the reproduction of inequalities already started, and the lack of freedom was increasingly keenly felt. The structure of new capitalism seems to be based on capital ownership and the position on the labor market, though the old professional categories still have some validity. The new structure produces much larger inequalities and new forms of poverty. The threat of lasting poverty and exclusion looms large.